STRATEGI PEMASARAN DALAM BERHASILNYA PENGEMBANGAN TOKO ONLINE DENGAN PESAT PASCA COVID-19 PADA PERUSAHAAN M231 - Felicia, Safara; Siswanto, Bambang (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study digs deeper into the online marketing strategy carried out by the M231 company to develop and make it a success rapidly. This study provides new solutions and knowledge to other companies due to the drastic decline in sales experienced by all companies during the Covid-19 pandemic. The approach was carried out qualitatively, followed by interviews with three people related to online marketing from the M231 company. The method used was the IFA and EFA methods, then continued using the SWOT method. The results of the study provide the main strategies that can be carried out to develop online marketing rapidly, namely by always following and implementing viral trends. The quality and consistency of products and services are also other important factors in the success of online marketing